Enhancing Scientific Literacy and Gotong Royong through Culturally Responsive Problem-Based Learning with Gamification: A Classroom Action Research on Rotational Dynamics - Upik Laila Hanum; Arina Zaida Ilma; Rusmining, Rusmining; Sri Sundari (JURNAL PENDIDIKAN MIPA, 2026)
This classroom action research investigates the effectiveness of an integrated learning model combining Problem-Based Learning (PBL), Culturally Responsive Teaching (CRT), and educational gamification to enhance scientific literacy and gotong royong skills among 31 Grade XI students at SMA Negeri 1 Banguntapan, Yogyakarta. Using the Kemmis & McTaggart framework across two cycles on rotational dynamics, the intervention incorporated local Indonesian cultural elements (spinning top/gasing) and global contexts (ballet dance) into student worksheets and innovative games (“Who’s Fast, They Get It” in Cycle 1 and “Stop and Go Challenge” in Cycle 2) to accommodate kinesthetic learning styles and foster collaborative interdependence. Results showed moderate to significant improvements: scientific literacy scores rose from 55.16 (pre-cycle) to 89.78 (Cycle 2), with N-gain values of 0.35 (Cycle 1) and 0.44 (Cycle 2), while gotong royong skills increased from 75.32% to 79.57%, with the most notable gains in interpreting data and evidence scientifically, solidarity, and mutual encouragement. This study contributes a novel culturally grounded integrative model aligned with Indonesia’s Merdeka Curriculum and Pancasila Student Profile, providing empirical evidence that contextual gamified PBL effectively develops both cognitive and affective competencies in physics education.